2009
DOI: 10.1186/1471-2202-10-128
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulfate proteoglycans regulate the growth, differentiation and migration of multipotent neural precursor cells through the integrin signaling pathway

Abstract: Background: Neural precursor cells (NPCs) are defined by their ability to proliferate, self-renew, and retain the potential to differentiate into neurons and glia. Deciphering the factors that regulate their behaviors will greatly aid in their use as potential therapeutic agents or targets. Chondroitin sulfate proteoglycans (CSPGs) are prominent components of the extracellular matrix (ECM) in the central nervous system (CNS) and are assumed to play important roles in controlling neuronal differentiation and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 56 publications
4
71
0
Order By: Relevance
“…This is consistent with reports that neuronal differentiation is inhibited when neurons are exposed to amyloid-β (40). It has been demonstrated that changes to CSPG structure through sulfation can alter its function and role in neural differentiation (18). We have recently shown that the secondary structure of polysaccharides can be dramatically altered through a simple oxidative modification of the backbone, and this is accompanied by changes to nanotopography and macromolecular organization (41).…”
Section: Regions Of Amyloid Plaque Buildup In Alzheimer's Present Incsupporting
confidence: 77%
See 1 more Smart Citation
“…This is consistent with reports that neuronal differentiation is inhibited when neurons are exposed to amyloid-β (40). It has been demonstrated that changes to CSPG structure through sulfation can alter its function and role in neural differentiation (18). We have recently shown that the secondary structure of polysaccharides can be dramatically altered through a simple oxidative modification of the backbone, and this is accompanied by changes to nanotopography and macromolecular organization (41).…”
Section: Regions Of Amyloid Plaque Buildup In Alzheimer's Present Incsupporting
confidence: 77%
“…Interestingly, the changes to the physical aspects of a neuronal environment can originate from changes to morphology of support cells such as astrocytes and also changes to ECM structure and properties. Cells and ECM polysaccharides play an important role in growth, differentiation, and migration of neural precursors, as well as in repair and plasticity in the central nervous system (17,18). However, in addition to a biological function, cells and macromolecules provide a physically defined environment (19,20), and we postulate a significant role for topography in neural development.…”
mentioning
confidence: 99%
“…Interestingly, TNC 2/2 mice show a reduction in expression of ASCL1 (Mash1) by retinal stem/progenitor cells (Besser et al, 2012), in contrast to our study where TNR deficiency resulted in increased ASCL1 expression in NSCs in the ganglionic eminence. Enzymatic degradation of chondroitin sulfate expressed by proteoglycans in the stem cell niche promotes differentiation and migration of neural progenitor cells (Gu et al, 2009), indicating an influence of these extracellular matrix molecules on neurogenesis. The importance of the extracellular matrix in regulating neurogenesis has been supported by studies on matrix metalloproteinases, which can regulate neurogenesis by proteolytic modulation of extracellular matrix molecules (Bovetti et al, 2007;Kang et al, 2008;Tonti et al, 2009;Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a cognate receptor interacting with TNR in NSCs is b1 integrin, which is a prominent sensor of signaling from extracellular matrix components expressed by neural cells (Liao et al, 2008). b1 integrins are highly expressed in murine neurospheres (Gu et al, 2009), and more than 90% of human embryonic-stem-cellderived NSCs express b1 integrins (Ma et al, 2008). Blocking the functions of b1 integrin inhibits proliferation of NSCs (Ma et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of CSs and DSs by ChaseABC treatment, which unselectively cleaves CSs and DSs from CSDSPGs, impaired neurosphere formation, decreased proliferation of NSCs in vitro and in the ventricular zone of E14.5 mouse forebrains (Sirko et al, 2007), and diminished in vitro proliferation of NSCs derived from the E16 rat forebrain (Gu et al, 2009). Although the influence of different CS and DS patterns on NSCs has been reported by studying isolated CSs and DSs, these investigations made use of either chemically synthesized CS and DS oligosaccharides or CSs and DSs extracted mostly from non-neural organs, as well as from different animal species with features possibly different from those derived from neural tissues (Gama et al, 2006;Ida et al, 2006;Sato et al, 2008).…”
Section: Discussionmentioning
confidence: 99%